(untitled) (Sociologisk Forskning, 1994)
The Hidden History of Swedish Sociology - The Case of Gustaf Steffen According to the official history of Swedish sociology, it started in 1947 when Torgny Segerstedt was appointed professor in sociology at the University of Uppsala. This article treats the largely hidden history of Gustav Steffen (1864 - 1929), who was professor in sociology and economics in Gothenburg 1903-1929. Steffen was oriented towards Europe and lived many years in Germany, England and Italy. He worked as a correspondent for Swedish newspapers and he made several empirical studies of relevance for social policy. Steffen was also a social democrat and member of parliament. The sociology of Gustav Steffen was influenced by the philosopher Henri Bergson, especially his philosophy of intuition. According to Steffen, the most important task is to promote a life in close contact with both nature and society and combined with studies in philosophy and science. Today, when there is a renewed interest in the relation between professional knowledge and intuition, and in ecology and intuition, students in sociology should know more about this pioneer of Swedish sociology. Gustav Steffen was hidden partly for political reasons and partly because his sociology did not fit the scientistic ideal of the first generation of Swedish sociology. Today, times may be ripe for an appreciation of Gustav Steffen as a sociologist.